Influenza pandemic: perception of risk and individual precautions in a general population. Cross sectional study - Halvorsen Peder A; Kristiansen Ivar S; Gyrd-Hansen Dorte (BMC, 2007)
Abstract Background An influenza pandemic may have considerable impact on health and societal functioning. The aim of this study was to explore people's reflections on the consequences of a pandemic. Methods Cross-sectional web-based survey of 1,168 Norwegians aged 16-82 years. The main outcome measures were answers to questions about a potential pandemic ("serious influenza epidemic"): statements about personal precautions including stockpiling Tamiflu®, the perceived number of fatalities, the perceived effects of Tamiflu®, the sources of information about influenza and trust in public information. Results While 80% of the respondents stated that they would be "careful about personal hygiene", only a few would stay away from work (2%), or move to an isolated place (4%). While 27% of respondents were uncertain about the number of fatalities during an influenza pandemic, 48% thought it would be lower than the estimate of Norwegian health authorities (0.05%-1%) and only 3% higher. At least half of the respondents thought that Tamiflu® might reduce the mortality risk, but less than 1% had personally purchased the drug. The great majority had received their information from the mass media, and only 9% directly from health authorities. Still the majority (65%) trusted information from the authorities, and only 9% reported overt distrust. Conclusion In Norway, considerable proportions of people seem to consider the mortality risk during a pandemic less than health authorities do. Most people seem to be prepared to take some, but not especially disruptive, precautions.